2013
DOI: 10.1097/sla.0000000000000247
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of CTGF Single-Nucleotide Polymorphisms on Outcomes in Crohn's Disease

Abstract: These data implicate the rs6918698GG genotype with an age of disease onset of greater than 40 years in Crohn's disease whereas the rs9402373CC genotype is associated with a nonstricturing, nonpenetrating disease phenotype. CTGF SNPs do not influence the rate of recurrence after terminal ileal resection for Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The CC minor allele homozygote of CTGF variant rs6918698 is located in the promoter at -945 and is a significant risk factor for the progression of hepatitis C virus-related chronic liver disease, including hepatocellular carcinoma (36). The GG major allele homozygote of CTGF variant rs6918698 was associated with an older age of onset of Crohn's disease (37). A meta-analysis found that CTGF rs6918698 CG heterozygotes and minor allele CC homozygotes had a greatly decreased susceptibility to systemic sclerosis in Asian (38) and French (39) populations.…”
Section: Continuedmentioning
confidence: 99%
“…The CC minor allele homozygote of CTGF variant rs6918698 is located in the promoter at -945 and is a significant risk factor for the progression of hepatitis C virus-related chronic liver disease, including hepatocellular carcinoma (36). The GG major allele homozygote of CTGF variant rs6918698 was associated with an older age of onset of Crohn's disease (37). A meta-analysis found that CTGF rs6918698 CG heterozygotes and minor allele CC homozygotes had a greatly decreased susceptibility to systemic sclerosis in Asian (38) and French (39) populations.…”
Section: Continuedmentioning
confidence: 99%
“…FHypoMR 3 was associated with the connective tissue growth factor gene. The protein encoded by this gene is a mitogen which is involved in cell adhesion and chondrocyte proliferation and differentiation in multiple cell types (36). FHypoMR 4 was associated with the kinesin family member 1B gene.…”
Section: Resultsmentioning
confidence: 99%
“…Formalin fixation can induce DNA–protein crosslinkages which can prevent amplification; in addition, nucleic acid fragmentation may occur due to specimen aging or the pH of the fixative [32]. However, this technique is increasingly being employed successfully [14,33] and only amplifiable DNA was utilized in the current study. Furthermore, when compared with whole blood leucocytes, no‐call and discordant‐call rates are below concerning thresholds, showing that formalin‐fixed archival tissue is a viable DNA source for genomic analysis [34].…”
Section: Discussionmentioning
confidence: 99%
“…A generic genetic model (AA, AB, BB) and a dominant model (AA + AB > BB) was used to determine associations between individual SNPs and the development of colorectal cancer. The generic model is powered to detect an imbalance in any of the three genotypes and the dominant model is powered to detect a change in risk with one or both risk alleles present [14]. Kaplan–Meier estimates were calculated to examine recurrence rates.…”
Section: Methodsmentioning
confidence: 99%